The Kyoto Protocol: An economic and game theoretic interpretation - Parkash Chander; Henry Tulkens; Jean-Pascal Van Ypersele; Stephane Willems (Fondazione Eni Enrico Mattei (FEEM), 1999)
Calling upon both positive and normative economics, we attempt to characterise the issues at stake in the current international negotiations on climatic change. We begin (Section 2) by reviewing the main features of the Protocol. Then (Section 3), we identify by means of an elementary economic model the main concepts involved: optimality, non co-operation, coalitional stability. We observe (Section 4) that "business-as-usual", "no regrets" and other domestic policies are alternative ways to conceive of the non co-operative equilibrium prevailing before the negotiations. Which one should be retained? Data suggest that the prevailing situation is a mixed one, exhibiting characteristics of several of these policies. We then turn (Section 5) to interpreting the Protocol. While there is no firm basis to assert that the emission quotas chosen at Kyoto correspond to optimal emissions (although they are a step in the right direction), economic and game theoretical arguments are put forward to support the view that for achieving these emission quotas, trading ensures efficiency, as well as coalitional stability for the agreement provided it is adopted at the largest scale i.e. worldwide. Finally, it is argued in Section 6 that beyond the Kyoto Protocol, the achievement of coalitionally stable optimality at the world level is a real possibility with trading, provided agreement can be reached in the future as to appropriate reference emission levels, in particular as far as developing countries are concerned.
Keywords: 330; Internationale Umweltpolitik; Klimaschutz; Emissionshandel; Spieltheorie; Theorie; Welt